The identities of some subspecies, forms and individual specimens in museums previously classified as Melitaea phoebe ([Denis & Schiffermüller], 1775) (Lepidoptera: Nymphalidae) - Peter J. Russell; Antonio Vives Moreno (SHILAP, 2023)
The identities of further taxa associated previously with Melitaea phoebe: pseudosibina Alberti, 1969, allophylus Rütimeyer, 1942 and rubialesi Gómez Bustillo, 1973 are identified as M. phoebe, and M. ornata, respectively. Further specimens from the Gómez Bustillo collection housed in the Universidad Politécnica, E. T. S. Ingeniería de Montes, Forestal y del Medio Natural, Unidad de Entomología y Zoología, Madrid, Spain (UPM) and from the entomological reference collection of M. phoebe housed in the Museo Nacional de Ciencias Naturales, Madrid, Spain (MNCN), Universidad Autónoma de Madrid, Facultad de Ciencias, Departmento de Biología, Madrid, Spain (UAM) are reclassified as M. ornata. The distribution of M. ornata has been expanded to include locations in the Spanish Provinces of Cuenca, Guadalajara, Madrid, Palencia, Toledo, and Zaragoza.